Generation Z and ZIS: The Roles of Accountability, Transparency, and Fintech in Shaping Payment Intention at BAZNAS - Mustafa Kamal; Nirdukita Ratnawati; Hudan Baihaqi Malik; Susi Susanti (Jurnal Akuntansi dan Keuangan Islam, 2026)
This study examines the influence of accountability, transparency, and financial technology (fintech) on Generation Z's interest in paying Zakat, Infaq, and Sadaqah (ZIS) through the National Zakat Agency (BAZNAS). Using the Tawhidi String Relations (TSR) framework, this research emphasises the ethical and epistemic interconnection between institutional trust, technological advancement, and the maqasid-oriented behaviour of young Muslim donors. The study employs a quantitative associative approach using SEM-PLS and data collected from 173 purposively selected respondents. The results indicate that while accountability does not have a statistically significant impact on ZIS payment interest (t = 1.403; p = 0.161), transparency (t = 3.402; p = 0.001) and fintech (t = 3.780; p = 0.000) significantly enhance Generation Z’s willingness to contribute. These findings suggest that digital trust and systemic clarity, when aligned with the TSR principle of interconnectedness (shuratic process), can strengthen the ethical foundation and practical mechanisms of zakat institutions. The study contributes to Islamic socioeconomic discourse by bridging behavioural finance with Tawhidi epistemology, offering insights into sustainable and value-driven ZIS mobilisation in the digital age.